Observation on the Effect of High-Quality Nursing Intervention plus Health Education in Chemotherapy for Non-Small Cell Lung Cancer and Its Influence on the Physical and Mental Health of Patients. (18th August 2022) - Feng, Liyun; Yang, Dongmei
Abstract : Objective. The objective is to analyze the effect of high-quality nursing intervention combined with health education in the chemotherapy for non-small cell lung cancer and its impact on the physical and mental health of patients. Methods. The study included 136 patients with non-small cell lung cancer treated at our hospital from March 2020 to December 2021, who were divided into the observation group and the routine/control group by randomization, with 68 patients in each. All patients received the GP (gemcitabine + cisplatin) chemotherapy. The control group received routine nursing care, whereas the observation group received high-quality nursing care mixed with health education. The effect of nursing intervention, patient self-management, and the influence on the physical and mental health of the patients was compared between the two groups. Results. The total efficacy rate (89.71%) of the observation group was significantly higher than that of the routine group (57.35%) (P < 0.05 ). The self-management level of the patients in the observation group, indicated by the Exercise of Self-Care Agency (ESCA) score, was considerably higher than that of the regular group after nursing intervention. Similarly, the observation group's quality of life, which was evaluated in terms of physical function, role function, emotional function, cognitive function, social function, and overall health status, was much better than the routine group's. Furthermore, the SAS, SDS, and overall incidence of adverse events were lower in the observation group than in the regular group. (P < 0.05 ). Conclusion. The application of high-quality nursing intervention combined with health education in chemotherapy for non-small cell lung cancer has favorable clinical benefits, enhances patient compliance and self-management capacity, and exerts a positive influence on the patient's physical and mental health. Adverse reactions can provide a more trustworthy scientific basis for therapeutic therapy. The method should be widely used.